1987
DOI: 10.1111/j.1600-0714.1987.tb00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma of the oral cavity: clinicopathologic analysis of 20 cases

Abstract: Twenty cases of malignant lymphomas (ML) of the oral cavity were reviewed in the light of recent histologic classification. They occurred in 12 male and 8 female patients, with the age range of 11–80 years (median 51 years of age). Eighty percent of patients were stages IE and HE. Histologically, 15 cases (75%) were ordinary non‐Hodgkin's lymphoma (NHL) with diffuse large cell type being the most common. The remaining 5 cases, undefinable by classification scheme for ordinary NHL, were designated as malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
11

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 20 publications
0
20
0
11
Order By: Relevance
“…Malignant lymphomas of the oral cavity represent 5% of all lymphomas [3] and are most common among male patients between 50 to 70 years of age [4]. Hematologic malignancies are very often seen in immunocompromised patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant lymphomas of the oral cavity represent 5% of all lymphomas [3] and are most common among male patients between 50 to 70 years of age [4]. Hematologic malignancies are very often seen in immunocompromised patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is because in the latter situation, large-field abdominal irradiation alone is often limited by the intolerance of the abdominal organs and bone marrow, plus there is a lesser chance of a complete response to multidrug chemotherapy alone with bulky (than with nonbulky) tumors [10]. Recent literature [11,12] has shown that the unfavor able histologic type of lymphoma is associated with a relatively higher relapse rate and a worsened prog nosis. However, the efficacy of multiagent chemo therapy for the high-grade lymphoma variety has been reported in two past experiences [13,14], In summary, this communication presented the histopathology, management and survival in a small group of patients with malignant lymphoma which initially occurred in the retroperitoneal area.…”
Section: Discussionmentioning
confidence: 99%
“…Affected bony areas show a "punched out" pattern that is due to multiple areas of destruction with ill defined radiolucent lesion. Involvement of the maxillary sinus will cause opacification with eroded cortical walls and associated sinus mass (Fukuda, et al, 1987). The Ann Arbor staging system, originally designed for Hodgkin's disease, is used for NHL as evident above.…”
Section: Clinical Featuresmentioning
confidence: 99%